Correction: Gil-Almagro et al. Anxiety Evolution among Healthcare Workers—A Prospective Study Two Years after the Onset of the COVID-19 Pandemic Including Occupational and Psychoemotional Variables. Medicina 2024, 60, 1230 - Fernanda Gil-Almagro; Fernando José García-Hedrera; Cecilia Peñacoba-Puente; Francisco Javier Carmona-Monge (Medicina)
In the original publication [...]